Clinical, physiological, and psychological study of asthmatic children attending a hospital clinic. Issue 12 (December 1977) - Norrish, Mary; Tooley, Marian; Godfrey, Simon
Abstract : The results of an investigation into the relationship between clinical, physiological, and psychological factors in 63 children with asthma are reported. The children were classified according to the severity of their asthma by reference to their regular drug usage and also were assessed in terms of the quality of control of the asthma and the degree of compliance with medication. Lung function tests and exercise tests were also carried out. Standard questionnaires to detect emotional or behavioural `deviance' in the children were completed by their mothers and by class teachers and assessments made of their personalities and the mental health of their mothers. Though the percentage of children with deviant scores on the questionnaire was high, it was not much greater than had been found among other (nonasthmatic) London children. Resting peak flow rate, measured as the mean of at least three tests on different clinical attendances, reflected the clinical grading of severity. Deviant children had lower levels of peak flow than non-deviant children, but their bronchial lability as measured by exercise-induced asthma was similar. Poor control of the asthma was associated with emotional or behavioural deviance, whereas deviance was independent of the severity of the asthma per se .